Iron starvation induces apoptosis in rhizopus oryzae in vitro - Shirazi, Fazal (Virulence, 2015)
Mortality associated with mucormycosis remains high despite current antifungals. Iron-starvation strategies have been shown to have promising activity against Mucorales. We hypothesized that iron starvation enhances apoptosis in Rhizopus oryzae. Apoptosis was characterized in R. oryzae transformed with RNAi plasmid targeting FTR1 expression (iron permease mutant) or empty plasmid grown in iron rich (0.125% FeCl(3)) and iron depleted media (YNB+1mM ferrozine and 1 mM ascorbic acid). Increased apoptosis was observed with dihydrorhodamine-123 and rhodamine-123 staining in the iron starved mutant FTR1 when compared to empty plasmid, followed by increased extracellular ATP levels. In addition, DNA fragmentation and metacaspase activity were prominent in FTR1. In contrast, Rhizopus strains grown in iron-rich medium displayed minimal apoptosis. Our results demonstrate a metacaspase dependent apoptotic process in iron deprived condition and further support the role of iron starvation strategies as an adjunct treatment for mucormycosis, a mechanism by which iron starvation affects R. oryzae.